Epidemiological Investigation and Virus Tracing of a Measles Outbreak in Zhoushan Islands, China, 2019 - Zhang, Hui; Chen, Can; Tang, An; Wu, Bing; Liu, Leijie; Wu, Mingyu; Wang, Hongling (Frontiers in Public Health, 2020)
Abstract Background: Measles transmissions due to case importations challenged the globally public health systems and herd immunities in all countries. In 2019, an imported measles case and its subsequently outbreak was found in the Zhoushan Islands. Here, the process of epidemiological investigating and virus tracing were summarized to provide references for the prevention and control of measles in the future. Materials and Methods: The data on demographic, epidemiological and clinical manifestation of measles cases in this outbreak was collected. The 450-bp fragments of measles virus (MeV) N gene were amplified and sequenced. The genome of first imported case was further isolated. Then, the maximum-likelihood and time-scaled phylogenetic analysis were conducted. Results: The 28 measles cases were confirmed. Their onsets were between March 13 and May 18, 2019. The first patient was from Ukraine. He was confirmed at Fever Clinic in Zhoushan hospital on the March 15, 2019 and at the same time, the second case had visited here due to other illness and then 10 days later, the second case had onset. The majorities of followed cases (19/26) were clustered donggang street which was close to the Donggang farm product market where the second cases worked and the epidemic curve shows sustained community transmission. The 22 measles virus strains successfully isolated of this outbreak were all belonged to D8.2a sub-cluster and clustered with the KY120864/MVs/GirSomnath.IND/42.16/[D8]. The analysis of complete D8 genotype genome pointed that this prevailing strain was originated from the India in 2015 and its evolutionary rate was estimated as 6.91×10-4 (5.64 - 7.98×10-4) nucleotide substitutions/site/year. Conclusion: This outbreak was caused by an imported case from Ukraine. There was a possible nosocomial infection between the first case and the second case. Then, the second case play a important role in the spread of virus due to her occupation. The molecular phylogenetic analysis could help to track the origin of virus. To increase and maintain the high level of vaccination coverage (≥95%) and efficient response to imported cases are essential to prevent and control the recurrence and outbreak of measles virus.